Impact of human activities and building characteristics on indoor air quality in low-income urban settlement - Fathina Izmi Nugrahanti; Mochamad Donny Koerniawan; Dewi Larasti; Agustinus Adib Abadi; Müslüm Arıcı; Surjamanto Wonorahardjo (Journal of Air Pollution and Health)
Introduction: Poor Indoor Air Quality (IAQ) in the growing number of low- income urban houses is closely linked to their unstructured neighbourhood development, poor building quality and unique community behaviour. It has been associated with numerous health issues which determine the occupant’s quality of life. This study proposed an explanatory model to reveal the interactive effect of building, human, and environment, on IAQ in tropical urban houses. Materials and methods: Particulate Matter (PM), Carbon dioxide (CO₂), airflow, temperature, and relative humidity were continuously measured using calibrated sensors in two seasons. Data on the active ventilation openings, indoor characteristics (material, volume, layout, and indoor porosity), real- time activity, and occupant’s perception were recorded through questionnaire. Results: The average indoor PM10 and PM2.5 were 1.8 and 4.8 times higher than World Health Organization (WHO) standard, mostly affected by habitual indoor smoking which increase PM10 and PM2.5 by 259% and 281%. High cooking intensity increased kitchen CO₂ concentration by 47%. However, 82.75% of the occupants accepted this poor IAQ as neutral, which was correlated to their low education and economic backgrounds. Moreover, regression analysis showed significant effect of house volume, kitchen layout, and roof structure’s airtightness, on pollutant concentrations. Conclusion: Low-income occupants have habits and activities that generate high indoor contaminants, worsen by the confined living space with insufficient ventilation, resulting in poor IAQ. Hence, stakeholders should prioritise educating low-socioeconomic communities about the health risk of high indoor pollution. Beside human activity control, this study offers a new IAQ mitigation perspective on the impact of interior characteristics on pollutant accumulation and dilution inside buildings.